2022
DOI: 10.1186/s41687-022-00469-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of patient- and proxy-reported outcomes for children with impairment of the upper extremity: a systematic review using the COSMIN methodology

Abstract: Background As patient-reported outcome measures (PROMs) have become of significant importance in patient evaluation, adequately selecting the appropriate instrument is an integral part of pediatric orthopedic research and clinical practice. This systematic review provides a comprehensive overview of PROMs targeted at children with impairment of the upper limb, and critically appraises and summarizes the quality of their measurement properties by applying the COnsensus-based Standards for select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Among the 10 Arabic PROMs included in the review, none demonstrated sufficient properties for all psychometrics described in COMSIN guidelines. Our findings are consistent with the findings of previous systematic reviews that used COMSIN tools to assess the methodological quality of pediatric PROMs for participation [ 32 ], upper limb impairments [ 33 ], and pain [ 34 ]. All reviews concluded that the methodological quality of the PROMs reviewed did not reach sufficient psychometrics properties.…”
Section: Discussionsupporting
confidence: 91%
“…Among the 10 Arabic PROMs included in the review, none demonstrated sufficient properties for all psychometrics described in COMSIN guidelines. Our findings are consistent with the findings of previous systematic reviews that used COMSIN tools to assess the methodological quality of pediatric PROMs for participation [ 32 ], upper limb impairments [ 33 ], and pain [ 34 ]. All reviews concluded that the methodological quality of the PROMs reviewed did not reach sufficient psychometrics properties.…”
Section: Discussionsupporting
confidence: 91%
“…This systematic review is a continuation of the joined effort to provide a comprehensive overview of the evidence on the psychometric properties of PROMs used for both upper and lower extremities. 9 , 10 With the use of the updated COSMIN methodology, to ensure a high-quality assessment, a total of 6919 publications were screened, resulting in 13 PROMs reporting a total of 112 psychometric properties. The results of this study increase the knowledge on proper use of PROMs through an evidence-based review and extensive recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive overview of PROMs used for evaluating upper extremity problems has been previously published as part of this joint effort. 9 This review will provide an extensive overview of PROMs used in orthopedic patients with a lower extremity impairment.…”
Section: Introductionmentioning
confidence: 99%
“…parent, primary caregiver). They are an integral part of patient‐centered care and increasingly important in understanding treatment effectiveness 1,2 . The usefulness of any outcome assessment is dependent on the strength of its psychometric properties, that is, validity, reliability, and responsiveness to change 3,4 .…”
Section: Domain Name Items Rating Response Options (Level) Modifier M...mentioning
confidence: 99%
“…They are an integral part of patient-centered care and increasingly important in understanding treatment effectiveness. 1,2 The usefulness of any outcome assessment is dependent on the strength of its psychometric properties, that is, validity, reliability, and responsiveness to change. 3,4 Many of the patient-reported outcome measures (PROMs) available for children with cerebral palsy (CP) demonstrate insufficient evidence of psychometric properties 5-8 and do not meet the COnsensus-based Standards for the selection of health Measurement INstruments.…”
mentioning
confidence: 99%